Effectiveness of Human Capital, Social Capital, And Innovation For Per-formance Improvement - Lewaherilla, Novalien Carolina; Sijabat, Asiani; Siahainenia, Selfiena; Huwae, Victor Ernest; Siahainenia, Ashwin (Eduvest - Journal of Universal Studies, 2023)
The study explores various concepts such as human capital, social capital, innovation capability, and performance. Human capital, involving skills, knowledge, and abilities, is crucial for organizational performance, and the higher level of education positively associates with better performance. Social capital encompasses networks, relationships, and shared norms that facilitate innovation by fostering an environment conducive to the exchange of ideas and resources. Innovation capability refers to an organization's capacity to adopt and employ technology to develop products, services, or processes that contribute to competitiveness and adaptability. This study formulates hypotheses aiming to establish relationships between human capital, social capital, innovation capability, and organizational performance. The proposed hypotheses suggest the influence of human capital and social capital on innovation capability and performance. A quantitative approach was utilized through explanatory research, investigating specific populations within Telkom Ambon Branch, using Partial Least Square (PLS) analysis. The study’s findings present insightful conclusions regarding the relationships between the variables. Human capital positively influences performance and innovation capability, while social capital has a positive effect on innovation capabilities but negatively impacts employee performance. Moreover, innovation capability positively impacts organizational performance. The examination further elucidates the mediation role of innovation capability between human capital, social capital, and employee performance. This study provides a comprehensive analysis of the relationships between human capital, social capital, innovation capability, and performance within an organizational context. The study's outcomes offer valuable insights for management and decision-makers in fostering sustainable competitive advantages and driving innovation within organizations.